Hear no Evil, See no Evil, Speak no Evil: The Secretisation of Information by Government in Australia - Kylie Weston-Scheuber (Bond Law Review, 2022)
This article draws together commentary and recent examples in relation to state secrecy provisions in a range of different areas, and considers the use of secrecy by the government in Australia, with some relevant comparisons to other common law countries. This extends beyond the secrecy offences that would ordinarily be referred to under the umbrella of “state secrecy” to other laws that may be utilised to keep government information secret, for example closed court orders and freedom of information exemptions. Broadly, the article outlines a series of laws and patterns of decision-making that together combine to effect an approach to the free flow of information of “Hear no evil, speak no evil, see no evil”.